1995
DOI: 10.1103/physreva.51.3053
|View full text |Cite
|
Sign up to set email alerts
|

Autoionizing states of the ytterbium atom by three-photon polarization spectroscopy

Abstract: The autoionizing states of ytterbium (Yb) were investigated by three-photon polarization spectroscopy. Ytterbium atoms were excited to autoionizing states through the transition 6s 'So -6s6p P, 4f' -( F7/2)6s 6p3/2 (J =2). The total angular momenta J of the autoionizing states were identified by comparing the line intensities from the spectra recorded with different combinations of the laser polarization. In this work, 17 autoionizing states including many new ones were investigated. For all these states Fano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…This fact in principle largely explains unusual and very rich physics of the AS in the lanthanide (rare-earth) atoms. Furthermore in Tables 6 and 7 [24,25] and references therein).…”
Section: Rare Earth Elementmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact in principle largely explains unusual and very rich physics of the AS in the lanthanide (rare-earth) atoms. Furthermore in Tables 6 and 7 [24,25] and references therein).…”
Section: Rare Earth Elementmentioning
confidence: 99%
“…In Refs. [24,25], the methods of twophoton ionization and three-photon polarization spectroscopy have been applied to studying the autoionization states (ASs) of the ytterbium atom. The ytterbium atom in the 6s 21 S 0 ground state was excited to the 6s6p 3 P 1 excited state by a photon with a visible wavelength (555.648 nm), and it was ionized by absorbing an ultraviolet photon with a wavelength of 260-285 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Aymar and co-workers presented theoretical analysis of highly excited levels of Yb, and investigated high-lying odd-parity levels Yb I by the method of selective three--step laser spectroscopy [23,24]. The interchannel interaction between single excitation from 4f 14 and double excitation from 6s 2 in Yb I was reported by Baig and Connerade [25]. Eliav et al calculated transition energies of ytterbium using the relativistic coupled-cluster method [26].…”
Section: Introductionmentioning
confidence: 99%
“…Maeda et al studied optical-microwave double-resonance spectroscopy of * corresponding author; e-mail: lozdemir@sakarya.edu.tr highly excited Rydberg states of ytterbium [13]. Yi and co-workers investigated autoionizing states of ytterbium atom [14,15]. Baig et al reported innershell and double excitation spectrum of ytterbium involving the 4f and 6s subshells [16].…”
Section: Introductionmentioning
confidence: 99%
“…Optical-microwave double-resonance spectroscopy of highly excited Rydberg states of ytterbium was studied by Maeda et al [13]. Yi and co-workers [14,15] investigated autoionizing states of the ytterbium atom. Baig et al [16] reported inner shell and double excitation spectra of ytterbium involving the 4f and 6s subshells.…”
Section: Introductionmentioning
confidence: 99%